2018
DOI: 10.1108/jkm-04-2017-0131
|View full text |Cite
|
Sign up to set email alerts
|

Inter-organizational social capital as an antecedent of a firm’s knowledge identification capability and external knowledge acquisition

Abstract: Purpose This paper concentrates on the antecedents of external knowledge acquisition of companies based on their inter-organizational relationships. Specifically, it considers social capital (i.e., the result of a firm’s inter-organizational relationships) as an essential precursor of knowledge identification capabilities and deliberated knowledge acquisition strategies. This study aims to propose that cognitive and relational dimensions of a firm’s inter-organizational social capital are mediating factors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 111 publications
5
73
0
1
Order By: Relevance
“…At this point, it is also important to differentiate between PACAP and RACAP and the role they play regarding knowledge acquisition and its exploitation by firms. While PACAP is closely connected with knowledge identification and assimilation, and inter-organizational relationships are thus essential aspects for detecting sources to acquire knowledge, RACAP is more dependent on internal processes to learn how to exploit the acquired knowledge ( Ortiz et al, 2018 ). These internally learned processes are guided by the way a company is able to manage employees’ interactions to transfer tacit and codified knowledge by means of networks based on trust and shared understandings about behaviors, the functioning of activities and its competitive objectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, it is also important to differentiate between PACAP and RACAP and the role they play regarding knowledge acquisition and its exploitation by firms. While PACAP is closely connected with knowledge identification and assimilation, and inter-organizational relationships are thus essential aspects for detecting sources to acquire knowledge, RACAP is more dependent on internal processes to learn how to exploit the acquired knowledge ( Ortiz et al, 2018 ). These internally learned processes are guided by the way a company is able to manage employees’ interactions to transfer tacit and codified knowledge by means of networks based on trust and shared understandings about behaviors, the functioning of activities and its competitive objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown, from a qualitative point of view, how internal SC positively impacts performance in knowledge-intensive contexts ( Salas−Vallina et al, 2020 ). Other papers have analyzed the relationships between SC and PACP (knowledge identification capability and external knowledge acquisition) ( Ortiz et al, 2017 , 2018 ), and others have focused on examining the mediating role of absorptive capacity (PACAP and RACAP) on the relationship of SC and innovation ( Duodu and Rowlinson, 2019 ; Wang et al, 2020 ). However, most of them have focused on analyzing SC from an external or inter-organizational point of view.…”
Section: Introductionmentioning
confidence: 99%
“…In [76], Franco tested the impact of relations and compatibility, and interactions between partners and found these factors to significantly and positively impact on alliance success; relations and compatibility refer to trust, lack of opportunistic behaviour, good relationships, informal links and commitment; interactions between partners refer to joint decision-making and exchange of ideas and knowledge between participants. Many studies on inter-organisational networks highlighted that the success of these networks is based on relational governance [77][78][79][80][81] and social capital [82][83][84], which enable inter-organisational knowledge transfer [85,86].…”
Section: The Firm and Its Network: Business And Cross-sector Collabormentioning
confidence: 99%
“…In addition, knowledge acquisition is an important approach for enterprises to overcome organizational inertia [2] and take the initiative to seek for new product development, which may satisfy the environment-friendly demands of the market, improve their environmental performance, enhance their green image, and increase profit. As was indicated by Ortiz et al [33], enterprises must strengthen knowledge acquisition, so as to rapidly respond to and timely update technical change, competition, and client demand in the dynamic environment. Studies show that enterprises' understanding of market and technical knowledge may increase their potential for discovering new opportunities and effectively using them [34,35].…”
Section: External Knowledge Acquisition and Corporate Performancementioning
confidence: 99%